Teaching What You're Not : Identity Politics in Higher Education. - Mayberry, Katherine (NYU Press, 1996)
Can whites teach African-American literature effectively and legitimately? What is at issue when a man teaches a women's studies course? How effectively can a straight woman educate students about gay and lesbian history? What are the political implications of the study of the colonizers by the colonized? More generally, how does the identity of an educator affect his or her credibility with students and with other educators?. In incident after well-publicized incident, these abstract questions have turned up in America's classrooms and in national media, often trivialized as the latest examples.